BAP1 regulates epigenetic switch from pluripotency to differentiation in developmental lineages giving rise to BAP1-mutant cancers - Kuznetsov, Jeffim N. (2019)
The BAP1 tumor suppressor is mutated in many human cancers such as uveal melanoma, leading to poor patient outcome. It remains unclear how BAP1 functions in normal biology or how its loss promotes cancer progression. Here, we show that Bap1 is critical for commitment to ectoderm, mesoderm, and neural crest lineages during Xenopus laevis development. Bap1 loss causes transcriptional silencing and failure of H3K27ac to accumulate at promoters of key genes regulating pluripotency-to-commitment transition, similar to findings in uveal melanoma. The Bap1-deficient phenotype can be rescued with human BAP1, by pharmacologic inhibition of histone deacetylase (HDAC) activity or by specific knockdown of Hdac4. Similarly, BAP1-deficient uveal melanoma cells are preferentially vulnerable to HDAC4 depletion. These findings show that Bap1 regulates lineage commitment through H3K27ac-mediated transcriptional activation, at least in part, by modulation of Hdac4, and they provide insights into how BAP1 loss promotes cancer progression.